2022
DOI: 10.1080/21655979.2022.2077893
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenine- induced LINC00667 promoted breast cancer progression through m6A/KIAA1429 positive feedback loop

Abstract: Increasing evidence supports that N 6 -methyladenine (m 6 A) and long noncoding RNAs (lncRNAs) both act as master regulators involved in breast cancer (BC) tumorigenesis at epigenetic modification level. Here, our research tries to unveil the interaction of m 6 A and lncRNAs on BC progression and explore the underlying regulatory mechanism. In the current study, we found that LINC00667 was m 6 A-modified lncRNA, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…KIAA1429 targets the m6A modification site of LINC00667 and increases its mRNA stability, forming a KIAA1429/m6A/LINC00667/miR-556-5p feedback circuit that accelerates BC progression. 43 Furthermore, bioinformatics analysis combined with RIP and Methylation-specific PCR (MSP) assays indicated that in BC cell lines (MCF-7, T47D, and MDA-MB-231), the highly expressed LncRNA urothelial carcinoma-associated 1(UCA1) recruited DNA methyltransferases to the METTL14 promoter region, thereby inhibiting the expression of METTL14. the down-regulated METTL14 suppressed the m6A modification of miR-375, which altered the expression of the downstream target SOX12.…”
Section: Lncrnas Regulate M6a In Bcmentioning
confidence: 99%
See 3 more Smart Citations
“…KIAA1429 targets the m6A modification site of LINC00667 and increases its mRNA stability, forming a KIAA1429/m6A/LINC00667/miR-556-5p feedback circuit that accelerates BC progression. 43 Furthermore, bioinformatics analysis combined with RIP and Methylation-specific PCR (MSP) assays indicated that in BC cell lines (MCF-7, T47D, and MDA-MB-231), the highly expressed LncRNA urothelial carcinoma-associated 1(UCA1) recruited DNA methyltransferases to the METTL14 promoter region, thereby inhibiting the expression of METTL14. the down-regulated METTL14 suppressed the m6A modification of miR-375, which altered the expression of the downstream target SOX12.…”
Section: Lncrnas Regulate M6a In Bcmentioning
confidence: 99%
“…LINC00667 functions as a sponge for miR-556-5p and positively regulates KIAA1429, resulting in a regenerative feedback loop of KIAA1429/m6A/LINC00667/ miR-556-5p that promotes BC progression. 43 In SKBR3 cells, VIRMA upregulates m6A-modified lncRNA NEAT1, which accelerates BC cell proliferation. 73 In contrast, certain lncRNAs regulated by m6A…”
Section: Regulation Of Lncrnas By M6amentioning
confidence: 99%
See 2 more Smart Citations
“…108 Lastly, m6A-induced LINC00667 promotes BC progression by a positive feedback loop involving m6A and KIAA1429. 133 In 2004, Luciano and colleagues provided the inaugural evidence of miRNA editing, reporting A-to-I conversion within the miR-22…”
Section: Mirna Expression Undergoes Rigorous Regulation At Both Trans...mentioning
confidence: 99%